Influence of beetroot supplementation on oxygen muscle saturation of semi-professional soccer players following a repeated sprint test - Michailidis, Y. (Central European Journal of Sport Sciences and Medicine, 2023)
Dietary nitrates have hemodynamic and metabolic effects on the body. This study aimed to investigate nitrate intake's effect on quadricep muscle oxygen saturation (StO2) of semi-professional soccer players during a repeated speed test (RSA). In a randomized, crossover design, 10 semi-professional soccer men players (21.3 ± 0.9yrs) performed two conditions: In one they consumed a nitrate-rich concentrated beetroot juice (250 mL/150 mg of NO3-) and in the other a placebo, 2h before a repeated sprint test. StO2 of the right vastus lateralis muscle was measured by near-infrared spectroscopy. A paired samples t-test was used to compute any differences in the subjects` performance on the StO2 and on RSA test. The level of significance was set at p < 0.05. The supplementation of nitrates limited the decrease in muscle oxygenation during the six sprints of RSA test (p < 0.001) and also, there seemed to be a tendency for limited the decrement of performance on RSA test (t = -1.586, p = 0.157, ?2 = 0.218). In conclusion, acute nitrate supplementation reduces the decrement of muscle oxygenation during exercise with repeated sprints and leads to a tendency of fatigue resistance during repeated sprints under controlled situations. Nitrate supplementation may have an ergogenic effect during exercise with repeated sprints via the higher muscle oxygenation.